Mitochondrial genome of bamboo rat Rhizomys pruinosus. (October 2014) - Zhao, Fang; Zhang, Tongzuo; Su, Jianping; Nevo, Eviatar; Lin, Gonghua
Abstract Bamboo rats are a group of subterranean rodents some of which feed on the roots and shoots of bamboo and other plants. In this study, we sequence the mitochondrial genome of a hoary bamboo rat Rhizomys pruinosus from the south of China. The genome is 16, 575 bp in length, and had a gene content of 13 protein coding, 22 tRNAs and 2 rRNAs. The overall base composition is 30.94% T, 24.83% C, 32.21% A and 12.02% G, with an A + T bias of 63.15%. The cytochrome genes were the most conservative genes compared with plateau zokor (Eospalax baileyi) and blind mole rats (Spalax carmeli) in the family Spalacidae. These mitochondrial data are potentially important for the study of molecular evolution, conservation genetics, agricultural technology and epidemiology.